PUBLIC MIND AGAINST COVID-19: HUMAN FOUNDATION TO COPE WITH HAZARDOUS CRISES - Srinonyang, Pradit (วารสารศรีล้านช้างปริทรรศน์, 2020)
The objective of this academic article was to consider how to deal with destructive disasters like the covid-19 pandemic by public-minded people in the global community. Public-mindedness was regarded as a morality, which was suitable for people during the terrible crisis because duties and responsibilities based on public consciousness assisted people to stay home and stay safe without an opportunity to infect a novel deadly coronavirus. At the same time, involved persons – patients, doctors, nurses, public heal officials, mass media, social media, state agencies, private sectors, the country’s government and foreign countries - performed their jobs with awareness of public health prevention, including inspection, observation, supervision, close watch of the Covid-19 disease as well as other disasters of mass destruction.